Integrasi Pemikiran Hamka dalam Pembelajaran Akidah di Indonesia (Studi di Universitas Muhammadiyah Prof. Dr. Hamka Jakarta) - Muhammad Dwi Fajri; Didin Saepudin; Bahrudin Bahrudin; Ibdalsyah Ibdalsyah (MUADDIB Jurnal Kependidikan dan Keislaman, 2022)
This study aims to reveal Hamka's thoughts and their integration into learning the creed at Muhammadiyah University in Indonesia. This research is qualitative, namely in the form of library research. This research was conducted at Muhammadiyah University, Prof. Dr. Hamka (Uhamka), Jakarta. The primary data sources are the Semester Learning Plan (RPS) document for the Uhamka Aqidah Course, Tafsir al-Azhar, Akhlaqul Karimah books, Budi Institute books, Living Institute books, Modern Sufism books, and other Hamka works. While the secondary data sources are other books that are relevant to the object of discussion in this study, Data analysis techniques were both empirical and theoretical. The results of this study show that the presentation of the faith material written by Hamka is not entirely the same as the presentation of the SRP for the faith courses at Uhamka. However, this study found that substantively, Hamka's messages related to faith education in Uhamka's lesson plans are scattered throughout his various works and can be integrated into aqidah lectures at Uhamka. Among Hamka's thoughts about Aqidah, which are substantively taught at Uhamka, is that Aqidah-monotheism is not just a belief but must be implemented in the lives of individuals, professions, families, communities, and even nations and humanity. Aqidah learning, which is oriented towards strengthening the implementation of character in life at Uhamka, is relevant to Hamka's view that a strong Aqidah-Tawhid will have an impact on the life of a Muslim in his vertical dimension with Allah SWT as well as its horizontal social dimension with fellow human beings and their environment.